The reality of bullying against academically gifted students from the point of view of teachers in general education schools in the State of Kuwait - ALenezi, Salamah Ajaj (Journal of Educational and Psychological Sciences, 2023)
The aim of the study is to identify the reality of bullying against academically gifted students from the point of view of teachers in general education schools in the State of Kuwait. The study sample consisted of (633) male and female teachers in general education schools in the intermediate and secondary stages. The bullying behaviour scale was built by the researcher in its four forms (psychological bullying, verbal bullying, social bullying, physical bullying), and finding indications of the validity and reliability of the scale. The researcher used the descriptive survey method for this study. The results of the study showed that the level of bullying among gifted students from the point of view of teachers in general education schools in the State of Kuwait was low for the scale. Very, and finally the physical bullying came at a very low level.The results of the study showed that there were no statistically significant differences in all forms of bullying due to the gender variable. As for the educational stage variable, the results showed that there were no statistically significant differences in the three forms of bullying (psychological - verbal - social), while there were statistically significant differences in bullying. physical for middle school.The study recommended the need to measure the level of bullying in the school during separate periods of the school year and in the light of the measurement result, the necessary measures and appropriate methods are taken, and work to raise awareness of the harms of bullying in the intermediate stage to reduce the various forms of bullying, especially physical bullying.
Keywords: School Bullying; Academically Gifted; General Education Schools